Hipolito Unanue and the hero’s construction. Analysis of the state-nation and Peruvian society relation in the cultural sphere - Casalino-Sen, Carlota (2005)
In October 1927, Hipolito Unanue’s mortal remains were exhumed and then burried again at the Illustrious Citizens’ Pantheon. This event was accompanied by various public acts directed to transform the physician Hipolito Unanue into a founding hero. The paper analyzes the various influencing contexts and factors. It emphasizes on two elements: the cult-organized community on the hero’s remembrance and what he represented to medical doctors and the Peruvian society. From the time Unanue died, the cult-organized community on this personage increases, consolidates and formalizes. So, from a spontaneous attitude of his closer family on building a mausoleum, we observe the following incorporation of the Faculty of Medicine, the Independence Founders Patriotic Society, and the medical College and Union. The Journal Hipolito Unanue would also play an important role. Unanue is perceived by the beginning of the XX century physicians as the paradigm of the successful professional that modernizes both teaching and practice of medicine. Also, as a high official accessing high power social stratum he took decisions standing up to viceroys and the first republican governors. That is, we deal with someone who harmoniously combines his professional task with the capacity of acting directly on State decisions. In this way there is full empathy between Unanue and the generation that carried him to the Illustrious Citizens Pantheon.